Stepwise reduction of an asymmetric π-expanded pyracylene towards the crystalline radical trianion - Zhu, Yikun; Borstelmann, Jan; Neiss, Christian; Wei, Zheng; Görling, Andreas; Kivala, Milan; Petrukhina, Marina A. (Chemical science, 2025)
The chemical reduction of a pyracylene-hexa-peri-hexabenzocoronene-(HBC)-fused nanographene TPP was investigated with K and Rb metals to reveal its multi-electron acceptor abilities. The in situ reaction of TPP with the above alkali metals, monitored by UV-vis-NIR and 1H NMR spectroscopy, evidenced the stepwise reduction process. The use of different solvents and secondary ligands enabled isolation of single crystals of three different reduced states of TPP with 1, 2, and 3 electrons added to its π-system. This provided a unique set of carbanions with gradually increasing negative charge for in-depth structural analysis of the outcomes of controlled electron addition to a non-planar and asymmetric nanographene, using X-ray crystallographic, spectroscopic, and theoretical tools. EPR spectroscopy measurements of the mono- and triply-reduced TPP products revealed distinct EPR splitting patterns. DFT calculations demonstrated a notable difference in the spin density distribution of these two open-shell products and provided insights into experimental EPR data. Moreover, the influence of the counterions on the “naked” TPP anions was illustrated computationally.
Gesehen am 21.08.2025